2013
DOI: 10.1088/1367-2630/15/12/123031
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced upper critical fields in a new quasi-one-dimensional superconductor Nb2PdxSe5

Abstract: We report the discovery of superconductivity with T c = 5.5 K in Nb 2 Pd x Se 5 , in which one-dimensional (1D) Nb-Se chains existing along the b-direction hybridize each other to form the conducting b-c * plane. The magnetic susceptibility and specific heat data in both single crystal and polycrystal show evidence of bulk superconductivity. The resistivity, Hall coefficient and magneto-resistance data all indicate the presence of an energy scale T * = ∼50 K, which becomes systematically lowered under hydrosta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
77
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(91 citation statements)
references
References 54 publications
(71 reference statements)
14
77
0
Order By: Relevance
“…This value exceeds the Pauli paramagnetic limit Hc 2 (0) = 1.84T c by over 3 times [1][2][3][4]. The anisotropic upper critical field ( ~ 3) along with temperature dependent anisotropy was indicative of possible multiband superconductivity [1,5]. Concepts related to strong spin-orbit scattering and spin triplet pairing mechanism were invoked to explain the highest ever reported H c2 (0)/T c value [4,5].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…This value exceeds the Pauli paramagnetic limit Hc 2 (0) = 1.84T c by over 3 times [1][2][3][4]. The anisotropic upper critical field ( ~ 3) along with temperature dependent anisotropy was indicative of possible multiband superconductivity [1,5]. Concepts related to strong spin-orbit scattering and spin triplet pairing mechanism were invoked to explain the highest ever reported H c2 (0)/T c value [4,5].…”
Section: Introductionmentioning
confidence: 87%
“…The band structure calculations show that the Fermi surface of Nb 2 PdS 5 is composed of multiple sheets with both quasi-two-dimensional (Q2D) hole character and quasi-onedimensional (Q1D) sheets of both hole and electron character that may give rise to multiband superconductivity [1,5]. Multiband superconductivity is also predicted for similar quasi onedimensional isomorphic Nb 2 Pd x Se 5 and Ta 2 Pd x S 5 compounds [9,10].…”
Section: Introductionmentioning
confidence: 87%
“…6 To be consistent with Ref. 6, where synthesis of the crystals is discussed, we define a' and c* directions as [-2 0 1] and [1 0 2], respectively.…”
mentioning
confidence: 98%
“…11 Single crystals of these chalcogenide superconductors are all needle-like with a preferred growth direction along the b-axis of the monoclinic crystal structure. Theoretical calculations on some Q1D chalcogenide superconductors 6,10 have suggested that the Fermi surface in the normal state of the materials is strongly anisotropic and consists of multiple bands. In the superconducting state, chalcogenide superconductors are all found to have an extremely large upper critical field (H C2 ), which is strongly anisotropic and well above the BCS Pauli limit 6-11 similar to Q1D organic superconductors.…”
mentioning
confidence: 99%
See 1 more Smart Citation